The Relationship Between Risk-Taking Courage and The Creativity of Faculty of Economics Students in Developing Business Ideas - Hutagalung, Gracella Rosnah S; Wulandari, Artika; Siregar, Ade Mima Zakia; Sahfitri, Serly; Limbong, Novia Grace Christin; Hutasuhut, Saidun (Journal of Education Transportation and Business, 2025)
This study was conducted to analyze the relationship between risk-taking courage and student creativity in developing business ideas at the Faculty of Economics, State University of Medan. In an era of global competition that demands innovation, risk-taking courage is an important element in developing an entrepreneurial orientation, because the courage to face uncertainty is believed to encourage students to explore new ideas more creatively. This study used a quantitative method by distributing questionnaires to 98 respondents selected through a Simple Random Sampling technique. The data obtained were then tested using validity, reliability, normality, linearity, and Pearson correlation tests. The results showed that all instruments were in the valid and reliable categories, and the data met the requirements for correlational analysis. The main findings revealed a significant relationship between risk-taking courage and student creativity, indicated by a signifsicance value of 0.0013 0.05. However, the correlation coefficient value of 0.251 indicates that the relationship is relatively low. The results of this study are expected to provide input for educational institutions to develop entrepreneurship learning programs that can foster risk-taking courage and enhance creativity simultaneously.